2006
DOI: 10.1143/jpsj.75.023601
|View full text |Cite
|
Sign up to set email alerts
|

Facet Growth of 4He Crystal Induced by Acoustic Waves

Abstract: Very fast growth of the c-facet of a 4 He crystal was induced by acoustic waves. The growth velocity was larger at lower temperatures and saturated below about 400 mK. The velocity was proportional to the acoustic wave power. This fast growth cannot be explained by the spiral growth mechanism for the known value of the step mobility. We developed a step multiplication model for high-power acoustic waves and found reasonable agreement with the observed temperature and power dependence of the growth velocity.KEY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 10 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…The following is a summary of typical features observed in the experiment: 8) (1) The absolute value of the growth rate was two or three orders higher than that of the spiral growth mechanism. (2) The temperature dependence of the growth rate was unique: as temperature decreased, growth rate increased, but it saturated below about 400 mK and showed no temperature dependence down to 100 mK.…”
Section: Special Topicsmentioning
confidence: 98%
See 1 more Smart Citation
“…The following is a summary of typical features observed in the experiment: 8) (1) The absolute value of the growth rate was two or three orders higher than that of the spiral growth mechanism. (2) The temperature dependence of the growth rate was unique: as temperature decreased, growth rate increased, but it saturated below about 400 mK and showed no temperature dependence down to 100 mK.…”
Section: Special Topicsmentioning
confidence: 98%
“…They are all new phenomena and have only been investigated using acoustic wave and highly nonlinear phenomena which cannot be investigated by other methods. Most of the results presented here have already been published, [6][7][8][9] but here we offer more pictures that are not included in previous papers.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments were performed in a high pressure cell that was cooled with a dilution refrigerator [20][21][22]. The high-pressure cell had two optical windows through which the inside could be observed.…”
Section: Methodsmentioning
confidence: 99%
“…4 He quantum crystals in superfluid is the exceptional material to be manipulated by small driving forces such as heat, gravity, and flow [6-13], because they grow extremely fast at low temperatures and play a very important role in understanding the fundamental aspects of crystal growth physics [14][15][16][17]. In previous reports, we have demonstrated that acoustic radiation pressure, which is the small second-order acoustic force usually not relevant to the crystallization process [18,19], induces both growth and melting of 4 He crystals and is a very useful tool to manipulate the interface in a desired orientation, even to a large extent [17,[20][21][22].…”
mentioning
confidence: 99%
“…Figure 1 shows a schematic of the experimental setup. A 3 He- 4 He dilution refrigerator is used for the experiment [10,11]. The inside of the cell can be observed through several infrared filters and infrared absorption glass from the outside.…”
Section: Introductionmentioning
confidence: 99%